Компенсация вектора переменного магнитного момента электрооборудования с помощью электромагнита с составным ферромагнитным сердечником - Король, Е.Г.; Лупиков, В.С.; Середа, А.Г.; Рудас, Ю.Д. (Технічна електродинаміка, 2011)
The research results of vector compensation of magnetic moment in electrical equipment by electromagnetcompensator, consisted of a coil and composite ferromagnetic core are shown. The original construction of electromagnet-compensator with complex core, two parts of which are disposed orthogonally, is described. The variant of using a pair of the electromagnets for compensation of alternating magnetic moment in a three-phase circuit breaker is offered.